Comparison of Polar V800 with Healink R211B for the Purpose of Analyzing Heart Rate Variability. (October 2019) - Xu, Hong; Chen, Jingwen; Dai, Jingyue; Lin, Huiting; Zhang, Genxuan; Shi, Bo
Abstract: Heart rate variability (HRV) is generally accepted as the best method to evaluate the function of the human autonomic nervous system. This paper compares the differences between the Polar V800 and the Healink R211B in the application of HRV analysis. Twenty-nine healthy college students participated in the study. The data were recorded simultaneously by both devices from all the subjects in a resting state. After being processed, the RR interval (RRI) data for 26 of the cases from the two devices were imported into the Kubios HRV software and were approximately consistent in regards to the HRV parameters. There was no significant difference ( r > 0.99, p > 0.05) between the two devices except for the α1 parameter ( p = 0.021). For the other 3 cases, the Polar V800 RRI could not be corrected due to partially missing data. Therefore, the HRV analysis and comparison were not conducted. The results indicate that the Polar V800 and the Healink R211B combined with Kubios HRV software can be used for HRV analysis in the time domain, frequency domain and for partial nonlinear parameter analysis, except in cases where data were missed by the Polar V800. However, it should be noted that approximately 10% of the samples from the Polar V800 have more RRI values missing so the entire sample data could not be used for HRV analysis.